Autoimmune eye diseases in multiple sclerosis - M.L. Martínez Ginés; P. Rojas Lozano (Neurology Perspectives, 2025)
Introduction: The eye is a complex organ that can present complications related to autoimmune diseases, including multiple sclerosis (MS). Ocular manifestations may act as early indicators of autoimmune diseases, and their early diagnosis and treatment are essential to guaranteeing patients' quality of life. This review analyses the main autoimmune eye diseases associated with MS, focusing on intermediate uveitis and its personalised management. Development: MS-associated uveitis includes various forms of intraocular inflammation affecting different areas of the eye. The relationship between MS and uveitis is complex and involves shared immunological mechanisms and diagnostic and therapeutic challenges. The clinical presentation of uveitis varies from asymptomatic forms to severe vision-threatening complications. The treatment of uveitis involves careful assessment and the consideration of immunomodulatory or immunosuppressive treatment with a view to controlling inflammation and preventing visual sequelae. Conclusions: Treatment of MS-related uveitis is complex and requires a multidisciplinary approach. Advances in immunomodulatory therapy offer new treatment options, as well as challenges related to adverse reactions and disease management. Further research is needed to better understand the relationship between MS and eye diseases, and to optimise therapeutic strategies and improve patients' visual and neurological outcomes. Resumen: Introducción: El ojo es un órgano complejo que puede reflejar complicaciones relacionadas con enfermedades autoinmunes, incluida la esclerosis múltiple (EM). Las manifestaciones oculares pueden actuar como indicadores tempranos de enfermedades autoinmunitarias y su diagnóstico y tratamiento oportunos son cruciales para la calidad de vida del paciente. En esta revisión, se analizan las principales enfermedades autoinmunes oculares asociadas con la EM, centrándose en las uveítis intermedias y su manejo personalizado. Desarrollo: Las uveítis asociadas con la EM incluyen diversas formas de inflamación intraocular que afectan diferentes áreas del ojo. Existe una relación compleja entre la EM y las uveítis, involucrando mecanismos inmunológicos compartidos y desafíos diagnósticos y terapéuticos. La presentación clínica de las uveítis varía, desde formas asintomáticas hasta complicaciones graves que amenazan la visión. El tratamiento de estas uveítis implica una evaluación cuidadosa y la consideración de terapias inmunomoduladoras o inmunosupresoras, con el objetivo de controlar la inflamación y prevenir daños visuales. Conclusiones: El tratamiento de las uveítis asociadas a la EM es complejo y requiere un enfoque multidisciplinar. Los avances en terapias inmunomoduladoras ofrecen nuevas opciones, aunque también presentan desafíos en términos de efectos secundarios y manejo de la enfermedad. Se necesita más investigación para comprender mejor la relación entre la EM y las enfermedades oculares, así como para optimizar las estrategias terapéuticas y mejorar los resultados visuales y neurológicos de los pacientes.